2016
DOI: 10.1128/jvi.00947-16
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 2 Virion Host Shutoff Endoribonuclease Activity Is Required To Disrupt Stress Granule Formation

Abstract: We previously established that cells infected with herpes simplex virus 2 (HSV-2) are disrupted in their ability to form stress granules (SGs) in response to oxidative stress and that this disruption is mediated by virion host shutoff protein (vhs), a virionassociated endoribonuclease. Here, we test the requirement for vhs endoribonuclease activity in disruption of SG formation. We analyzed the ability of HSV-2 vhs carrying the point mutation D215N, which ablates its endoribonuclease activity, to disrupt SG fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 82 publications
(98 reference statements)
0
23
0
Order By: Relevance
“…In the course of drafting our manuscript for publication, Finnen and colleagues reported that viral vhs protein encoded by UL41 in herpes simplex virus type 2 (HSV-2) suppresses SG formation [ 78 ]. Although α-herpesvirus vhs and γ-herpesvirus vSOX are not homologs, both are RNA endonucleases and exert their host shutoff function by digesting host mRNAs [ 79 82 ] which are fundamental for SG formation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of drafting our manuscript for publication, Finnen and colleagues reported that viral vhs protein encoded by UL41 in herpes simplex virus type 2 (HSV-2) suppresses SG formation [ 78 ]. Although α-herpesvirus vhs and γ-herpesvirus vSOX are not homologs, both are RNA endonucleases and exert their host shutoff function by digesting host mRNAs [ 79 82 ] which are fundamental for SG formation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although α-herpesvirus vhs and γ-herpesvirus vSOX are not homologs, both are RNA endonucleases and exert their host shutoff function by digesting host mRNAs [ 79 82 ] which are fundamental for SG formation [ 8 ]. In assumption of KSHV vSOX encoded by viral ORF37 in blocking SG formation via a mechanism similar to HSV-2 vhs [ 78 ], we transfected both HEK293 and HeLa cells with a Flag-tagged KSHV vSOX expression vector for 24 h and stained the cells for TIA-1-specific SG formation in the presence or absence of vSOX after induction by arsenite for 30 min. We confirmed vSOX expression in HEK293 cells by anti-Flag antibody staining of HEK293 cells ( Fig 9A ) and by anti-Flag antibody Western blot ( Fig 9B ), but had difficulty to express vSOX in HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of SG formation by depletion of G3BP1 indeed suppressed type I IFN expression in response to infection with influenza A virus or Newcastle disease virus (NDV) (25, 26). The fact that many viral factors interfere with SG formation (2731) also supports an antiviral function of SGs.…”
Section: Introductionmentioning
confidence: 85%
“…Viral proteins that inhibit host gene expression, including nsp1 of CoV (49)(50)(51), are often major virulence factors (70)(71)(72)(73)(74)(75)(76)(77)(78)(79). Accordingly, it is likely that MERS-CoV nsp1 also plays a critical role in MERS-CoV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Herpes simplex virus 1 and 2 virion host shutoff protein, Kaposi's sarcomaassociated herpesvirus SOX, and influenza A virus PA-X are virus-encoded RNases that induce endonucleolytic cleavage of host mRNAs, leading to host mRNA degradation (84,85). These viral endonucleases contribute to evasion of host antiviral responses, including IFN response and stress granule formation, and contribute to viral pathogenesis (70)(71)(72)(73)(74)(75)(76)(77)(78)(79), while roles of these virus-encoded endonucleases in production of virus particle have not been explored. To our knowledge, MERS-CoV nsp1 represents the first viral protein whose RNA cleavage-inducing function promotes virus assembly/budding.…”
Section: Discussionmentioning
confidence: 99%